2021
DOI: 10.1080/1406099x.2021.1920754
|View full text |Cite
|
Sign up to set email alerts
|

The investment behaviour of dairy farms in transition economies

Abstract: This article investigates dairy farm investment behaviour and the presence of soft budget constraints in the dairy farms of Baltic and Central European transition countries -Estonia, Hungary and Sloveniausing individual dairy farm accountancy panel data for the years 2007-2015. The empirical results confirm that gross dairy farm investment is positively associated with gross dairy farm investment for the previous year for financially unconstrained dairy farms, and negatively for financially constrained dairy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Similar to Fertő et al. (2020, 2021), we found that increase in debt to capital ratio decreases farm investments. While in agriculture, owned land is the main collateral for bank loans, the results suggest that farms with higher proportion of owned land invest less.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Similar to Fertő et al. (2020, 2021), we found that increase in debt to capital ratio decreases farm investments. While in agriculture, owned land is the main collateral for bank loans, the results suggest that farms with higher proportion of owned land invest less.…”
Section: Discussionsupporting
confidence: 81%
“…As in case of previous studies (Bakucs et al ., 2009; Bojnec and Latruffe, 2011; Aleksandrova, 2020; Fertő et al ., 2020, 2021), investment subsidies had a positive and significant effect on farm investments. This is in accordance with our expectations and the rationale of such a policy instrument.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…AGBENYO et al, (2019), in their contribution to the access to finance debate, established that understanding finance's function in the endogenous growth theory portrays that the agriculture sector's growth is dependent on access to financing. Access to financial services is also an essential to rural development, according to ABRAHAM &FONTA (2018) andFERTŐ et al, (2021). It will also increase incomes through productive investment, assist in the creation of employment opportunities, facilitate investments in health and education, and reduce the poor's vulnerability by assisting them in smoothing their income patterns over time (ASANTE-ADDO et al, 2017;BECK;DEMIRGUC-KUNT;HONOHAN, 2009;ISAGA, 2018).…”
Section: Introductionmentioning
confidence: 99%